2015
DOI: 10.1086/681106
|View full text |Cite
|
Sign up to set email alerts
|

Context dependency of top-down and bottom-up effects in a Northern Australian tropical river

Abstract: Top-down and bottom-up forces (consumer and resource limitation, respectively) influence biomass of primary producers and primary consumers in natural food webs. Few investigators experimentally examine both in concert, especially in the tropics. Tropical systems probably are more sensitive than temperate systems to eutrophication and other disturbances, such as destruction of riparian canopy cover, because of wide windows of ecological opportunity. We experimentally examined the relative importance of top-dow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 55 publications
0
6
1
Order By: Relevance
“…Our study also did not reveal a consistent pattern in macroinvertebrate diversity of above-and below-waterfall pools, suggesting that communities of shrimp and fish do not influence these biotic patterns; however, it is possible that fish and shrimp predators are substitutable and thus functionally redundant (sensu Ho & Dudgeon, 2016). In Northern Australia, Garcia et al (2015) found that top-down effects on macroinvertebrates were context dependent with respect to factors such as benthic habitat, stream velocity and community structure, each of which influenced invertebrate diversity. Ulu Temburong has frequent flood events; for example, after a storm, it is not uncommon for the level of Belalong to rise by 1 m in a 30-min period (Cranbrook, 1993).…”
Section: Discussioncontrasting
confidence: 60%
See 1 more Smart Citation
“…Our study also did not reveal a consistent pattern in macroinvertebrate diversity of above-and below-waterfall pools, suggesting that communities of shrimp and fish do not influence these biotic patterns; however, it is possible that fish and shrimp predators are substitutable and thus functionally redundant (sensu Ho & Dudgeon, 2016). In Northern Australia, Garcia et al (2015) found that top-down effects on macroinvertebrates were context dependent with respect to factors such as benthic habitat, stream velocity and community structure, each of which influenced invertebrate diversity. Ulu Temburong has frequent flood events; for example, after a storm, it is not uncommon for the level of Belalong to rise by 1 m in a 30-min period (Cranbrook, 1993).…”
Section: Discussioncontrasting
confidence: 60%
“…Moulton et al (2010) found that predacious fish inhibit shrimp and baetid mayflies from grazing in two Neotropical streams, thus increasing both abundance and quality of periphyton in pools containing fish. However, other experiments have found that top-down effects of fish on algae have less impact relative to bottom-up effects such as increases in nutrient levels (Garcia et al, 2015;Ho & Dudgeon, 2016). Interestingly, Ho & Dudgeon (2016) found no impact of high numbers of fish and shrimp on algal biomass or periphyton accumulation in three Hong Kong streams.…”
Section: Ecosystem Functionsmentioning
confidence: 90%
“…Disturbance due to environmental harshness (defined as “any relatively discrete event in time that removes organisms and opens up space which can be colonized by individuals of the same or different species” Townsend, , p. 38) can be a strong force structuring food webs through its influence on the strength of species interactions, resource availability and community composition (Peckarsky, McIntosh, Alvarez, & Moslemi, ; Wootton, ). However, the influence of such disturbance on the relative role of top‐down and bottom‐up processes in food webs is still not clear (Garcia, Townsend, & Douglas, Townsend & Douglas, ; Meserve, Kelt, Milstead, & Gutiérrez, ; Terborgh & Estes, ), despite being central to past debates about the relative roles of these processes (Gruner et al, ). Moreover, the frequency of extreme climatic events (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…As the base of benthic food webs, periphyton community structure and diversity can be widely used to assess the trophic state and thus can be used to support proposed best management practices (Matlock et al, 1999;Smucker and Vis, 2009;Grimmett and Lebkuecher, 2017). Generally, the development of periphyton in shallow lakes and rivers has been attributed to the changes of physical, chemical, and biological factors, including light availability (Warren et al, 2017), water velocity (Townsend et al, 2012), nutrient concentrations (Myrstener et al, 2018), grazing by consumers (Jones and Sayer, 2003;Garcia et al, 2015), etc.…”
Section: Introductionmentioning
confidence: 99%
“…Changes in the biomass and species composition of periphyton are regulated by biological groups, for example, invertebrates and vertebrate (Jones and Sayer, 2003;Cebrian et al, 2013). For example, benthic fish disturbance will potentially facilitate the release of nutrients from the sediment, thereby promoting periphyton growth (Meerhoff et al, 2007;Jeppesen et al, 2010), while invertebrates can remove periphyton biomass and alter community composition through direct grazing (Garcia et al, 2015;Mormul et al, 2017;Beck et al, 2019;Wolters et al, 2019).…”
Section: Introductionmentioning
confidence: 99%